Paracord Anklet and Bracelet Controls Against Mosquitoes - Deaniella Shaira Sembrano; Omeir Yasin; Ericka Shyn Guimbuayan; Joshua Dave Dalanon; Ih Robert John Cambel; Eric Manalo Jr.; Amera Malaco; Anamarie Valdez (ASEAN Journal of Science and Engineering, 2021)
The purpose of this study is to assess the effectiveness of paracord anklet and bracelet made up of guyabano (Annona Muricata) seeds and wormwood plant (Artemisia Absinthium) extract as mosquito repellent and to determine if the paracord anklet and bracelet can be as effective as the commercial patch used in this study. In the study, 2 groups were examined: The experimental group and the control group. The experimental group with variation 1 (50 guyabano seed, 80% of water, and wormwood extract), variation 2 (75 Guyabano seed, 50% of water, and wormwood extract), and variation 3 (100 Guyabano seed, 30% of water, and wormwood extract). The control group was tested with the commercialized patch. Results showed that the overall gathered data showed very promising effectiveness, with a level of effectiveness of 6.5 means. Furthermore, the ANOVA showed no differences at all between the Control and Experimental Group (fcalc 2.20fcrit3.49, P=0.13). This may therefore mean that the paracord anklet and bracelet made up of guyabano and wormwood plant is as effective as the commercial patch used in this study. This study shows that the paracord anklet and bracelet can be considered as an alternative and environmentally friendly mosquito repellent.